2023
DOI: 10.1007/s40820-023-01158-7
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional MXene/C Aerogels for Enhanced Microwave Absorption and Thermal Insulation

Abstract: Two-dimensional transition metal carbides and nitrides (MXene) have emerged as promising candidates for microwave absorption (MA) materials. However, they also have some drawbacks, such as poor impedance matching, high self-stacking tendency, and high density. To tackle these challenges, MXene nanosheets were incorporated into polyacrylonitrile (PAN) nanofibers and subsequently assembled into a three-dimensional (3D) network structure through PAN carbonization, yielding MXene/C aerogels. The 3D network effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(14 citation statements)
references
References 58 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…High porosity and low density of aerogels with nanomicro–multistage porous structure often result in good thermal insulation and thus are widely used as thermal insulation materials , or radiative cooling materials. ,,, It was found that adding acetone reduced the thermal conductivity of the PVA aerogel from 0.0492 to 0.0421 W/mK and reduced the thermal diffusion coefficient from 0.5815 to 0.5490 mm 2 /s (Figure f) resulting from the structural changes which increased the proportion of micro- and nanopores inside the aerogel and reduced the macro-gaps . Further, the incorporation of SiO 2 particles made the thermal conductivity decreased to 0.0390 W/mK and decreased the thermal diffusion coefficient to 0.4770 mm 2 /s.…”
Section: Resultsmentioning
confidence: 99%
“…High porosity and low density of aerogels with nanomicro–multistage porous structure often result in good thermal insulation and thus are widely used as thermal insulation materials , or radiative cooling materials. ,,, It was found that adding acetone reduced the thermal conductivity of the PVA aerogel from 0.0492 to 0.0421 W/mK and reduced the thermal diffusion coefficient from 0.5815 to 0.5490 mm 2 /s (Figure f) resulting from the structural changes which increased the proportion of micro- and nanopores inside the aerogel and reduced the macro-gaps . Further, the incorporation of SiO 2 particles made the thermal conductivity decreased to 0.0390 W/mK and decreased the thermal diffusion coefficient to 0.4770 mm 2 /s.…”
Section: Resultsmentioning
confidence: 99%
“…134 Stealth materials could not only reduce detection rate and improve their own survival rate but also increase aggression in order to obtain the most direct military benefits. 135 At present, stealth materials have been widely used in aircraft, main battle tanks, ships, arrows, and bombs. 136 For ground weapons, it is important to prevent attacks by airborne radar or infrared detection, radar-guided weapons, and laser-guided bombs.…”
Section: Applicationsmentioning
confidence: 99%
“…In military terms, microwave absorbing materials, which are also known as stealth materials, are an essential part of weapons and equipment systems . Stealth materials could not only reduce detection rate and improve their own survival rate but also increase aggression in order to obtain the most direct military benefits . At present, stealth materials have been widely used in aircraft, main battle tanks, ships, arrows, and bombs .…”
Section: Applicationsmentioning
confidence: 99%
“…The development of nanocomposites as broad-spectrum and efficient adsorbents with a simple preparation process has become a promising approach for the removal of various contaminants. Among these, three-dimensional (3D) graphene aerogels (GAs)-based composite adsorbents have attracted much attention due to their large specific surface area, porous structure, and abundant active sites. , To further improve the cleanup and photothermal conversion performances of GA-based adsorbents, incorporating GAs with two-dimensional (2D) MXene (transition metal carbon/nitride) has been recognized as an effective strategy, as MXene materials possess a unique nanostructure, exceptional adsorption capacity, strong light absorption ability, and high photothermal conversion efficiency. , MXene/GA composites have demonstrated superior performance compared to pristine GAs. , For instance, the adsorption capacities of V 2 CT X @GAs for methyl orange (MO) and methylene blue (MB) reached 160 and 142 mg·g –1 , respectively . Multifunctional Ti 3 C 2 T X /GAs can rapidly and effectively eliminate salt, organic pollutants, bacterium, and other contaminants in wastewater .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 MXene/GA composites have demonstrated superior performance compared to pristine GAs. 26,27 For instance, the adsorption capacities of V 2 CT X @GAs for methyl orange (MO) and methylene blue (MB) reached 160 and 142 mg•g −1 , respectively. 28 Multifunctional Ti 3 C 2 T X /GAs can rapidly and effectively eliminate salt, organic pollutants, bacterium, and other contaminants in wastewater.…”
Section: Introductionmentioning
confidence: 99%